EVALUASI KINERJA JIG TIPE PAN AMERICAN TERHADAP RECOVERY TIMAH HASIL PENCUCIAN BIJIH TIMAH PADA KAPAL ISAP PRODUKSI (KIP) TIMAH 17 DI LAUT TEMPILANG KABUPATEN BANGKA BARAT, PROVINSI BANGKA BELITUNG - Abror, Muhammad; Lagowa, Muhammad Ikrar; Hakim, Muhammad El (Jurnal Teknologi Mineral dan Batubara, 2024)
The early stage of mineral processing usually focuses mainly on recovery, not the grade of the concentrate. Tin dressing in Production Section Vessel on January 2023 did not meet target recovery of 96%. This study aimed to evaluate and optimize jig performance to achieve the desired target. The study focused on evaluating the configuration of variables such as feed velocity, bed thickness, as well as number and length of strokes. Measurement data of jig performance variables and tailings and concentrate samples were used as comparative data to the SOP. The calculation of the sample content was carried out through the grain counting analysis (GCA) method, which calculated the amount of concentrate and losses in each jig. The final results of washing recovery prior to washing evaluation were 92.70% Sn in observation I and 88.68% Sn in observation II, respectively. The washing process in observation I and II conditions were not considered optimal because the recovery had not reached the target. This is caused by variables that are not under the provisions To optimize the performance of the jig was the installation a comb in the flow section of the jig to standardize the flow that was too fast, remeasurement after the addition of the hematite stone, repairing pillow blocks and eccentric coupling bolts on the stroke length setting and resetting the variables in the jig performance following existing SOPs. After the evaluation and readjustment of the jig variables, the recovery was increased to 97.53% Sn. From this study it can be concluded that the failure to achieve the targeted recovery was caused by operational variables that did not meet the SOP including the length and number of strokes, bed thickness, and water flow rate due to technical constraints. After being repaired, the dressing recovery could meet or even exceed the recovery target.